Uma linhagem manchada pelo pecado. A representação e a estigmatização dos judeus-conversos a partir da perspectiva cristã (Castela, 1391-1478) - Follador, Kellen Jacobsen (2016)
This study aims at analyzing the social stigmatization of Christians from Jewish lineage, named conversos (New-Christians) in Coroa de Castela between 1391, when large part of the Jewish population was forced into Christian conversion, and 1478, when the Pope approved an inquisition court for the kingdom of Castela. After the conversions in 1391, part of the neophytes sought to be similar to the Christian community, in which they were considerably successful. Indications of stigmatization, however, had already started to emerge through the distinction between conversos and other Christians, who called themselves Old-Christians. The latter, guided by clear anti-Jewish prejudice heritage, considered the conversos as “other” Christians. The initial religious suspicion was added to social and political disputes that affected social relations negatively. Although not excluding the social and political factors, the hypothesis in this study is that the stigmatization of conversos was possible partly due to the religious and cultural concepts that some old-Christians had towards the conversos. To some Old-Christians, previously belonging to Judaism or the fact they descended from a lineage loyal to this religion prevented conversos from being considered legitimate Christians, which led to social stigmatization of many members in this group. In this setting, religious and cultural aspects of stigmatization can be identified in the discussion had in the kingdom of Castela, when the law known as Sentencia-Estatuto was created in 1449. It was intended to endorse prejudice and deny isonomy to conversos. In addition to this law, there were several accusations with religious and cultural features in satires and inquisition processes, which made it clear that the stigmatization of Christians from Jewish origin also had —besides social and political factors—influence of the cultural and religious framework common to Old-Christians during the study period.